New perspectives for performance analysis in sport with a radio frequency based system - Hökelmann, A.; Richter, K. (10th International Sport Sciences Congress, October 22-25, 2008, Bolu, Turkey, 2008)
Performance analysts have traditionally focused on team and match-play sports and various techniques have been effectively used to collect and analyse data in these sports (Hughes and Bartlett, 2002). Finding an indoor determining positions system that covers a large area in real time, is a desirable aim in the field off sports analysis. We tried to fulfil these requirements by using the radiofrequency LPM-system from ABATEC in combination with a therefore designed software tool. First we prove the accuracy of the System in static and dynamic conditions. Afterwards we show the opportunities of the system in field of sport at two different examples. By observing the trajectory of the gymnasts during rhythmic gymnastics choreography, we want to figure out how they use the regularized area. The other surveyed sport is handball and alpine skiing. In this field we proved if the system has the ability to analyse the play behaviour of the athletes during a game and to compare different skier or different runs.